PAQR5 drives the malignant progression and shapes the immunosuppressive microenvironment of hepatocellular carcinoma by activating the NF-κB signaling - Ruida Yang; Huanhuan Wang; Cong Wu; Yu Shi; Hanqi Li; Xinyue Bao; Yuqian Yang; Shaoshan Han; Xue Yang; Jie Tao; Hao Sun; Shaobo Wu; et al. (Biomarker Research)
Abstract Background Progesterone and adipose Q receptor 5 (PAQR5), a membrane receptor characterized by seven transmembrane domains, has been indirectly implicated in pro-carcinogenic activities, though its specific role in hepatocellular carcinoma (HCC) remains to be defined. Methods This study aimed to elucidate the molecular mechanisms by which PAQR5 facilitates HCC progression and contributes to the immunosuppressive microenvironment through an integrative approach combining multi-omics analysis and experimental validation. Utilizing data from bulk, single-cell, and spatial transcriptomics cohorts, this study systematically assessed the expression patterns, immune landscape, and functional characteristics of PAQR5 across different levels of resolution in HCC. Results PAQR5 expression was significantly upregulated in tumor tissues and correlated with poor clinical outcomes. Enrichment analysis revealed that PAQR5 activated the NF-κB signaling pathway in HCC. Single-cell transcriptomics identified PAQR5 as predominantly localized within malignant cell clusters, with significant association with NF-κB pathway activation. Spatial transcriptomics further corroborated the alignment of PAQR5 expression with tumor cell distribution. In vitro assays showed elevated PAQR5 levels in HCC cell lines, and silencing PAQR5 significantly suppressed cell proliferation, invasion, epithelial-mesenchymal transition (EMT), and prevented the formation of immunosuppressive microenvironment. In vivo studies demonstrated that targeting PAQR5 attenuated tumorigenic potential, disrupted the invasion-metastasis cascade and inhibited the tumor immune escape. Mechanistically, PAQR5 was found to activate NF-κB signaling by inducing ERK phosphorylation, thereby driving proliferation, invasion, EMT, and immune escape in HCC through the pathway.